Analysis of the Competitiveness of China-Thailand Tourism Service Trade - Huang, Zena (International Journal of Global Economics and Management, 2024)
This paper aims to conduct an in-depth analysis of the competitiveness of China-Thailand tourism service trade and explore the potential impact of visa exemption policies on the tourism service trade between the two countries. Through quantitative analysis methods, including Revealed Comparative Advantage (RCA), Trade Competitiveness Index (TC), and International Market Share (IMS), the study finds that Thailand has a significant international competitive advantage in the field of tourism service trade, while China is relatively at a competitive disadvantage. The paper further discusses the opportunities and challenges brought by visa exemption policies, pointing out issues such as self-media information dissemination, market openness, environmental sustainability, and service quality, and puts forward corresponding countermeasures and suggestions. Finally, the paper proposes future research directions, emphasizing the necessity of optimizing tourism service trade strategies in the context of globalization.